Rediseño del Sistema de Control de las Compuertas de la Antecámara y Desarenador de la Central Hidroeléctrica Canalete - Campos-Duarte, Edgar Jose (Instituto Tecnológico de Costa Rica, 2018)
Coopeguanacaste R.L is a company responsible for generating electricity to different sectors of the province of Guanacaste, currently Coopeguanacaste R.L has two power plants. One of them is the Bijagua Hydroelectric Power Plant and the other is the Canalete Hydroelectric Power Plant both located in the canton of Upala. The process of sand expelling in the Canalete H.P.P is done manually, which requires that an operator must move to the sand trap to carry out the process of sand expelling. This project consists on the modeling of the sluice gates of the desander section and the design of a system that allows to operate the antechamber gates both locally and remotely.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2018.
Keywords: PLC; Control; Adquisición; Datos; Sensores; Lógica; Automatización; Escaleras; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics